Minimizing Potential Damage To Butterworth To Optimize Tank Cleaning Processes At MT. Bro Combo - Romeo Dominggus Philia Sitompul; Dety Sutralinda; Romanda Annas Amrullah; Anak Agung Istri Sri Wahyuni (International Journal of Science and Environment (IJSE), 2026)
Butterworth is one of the main equipment in the tank cleaning process on tankers that plays a role in maintaining tank cleanliness before the next loading. Damage to the Butterworth can cause the tank cleaning process to be suboptimal, thus disrupting the smooth operation of the ship. This study aims to determine efforts to minimize potential damage to the Butterworth and identify obstacles that often occur during the tank cleaning process at MT. Bro Combo. The study used a qualitative method with data collection through observation, interviews, and documentation. The study population included all Butterworth maintenance activities and the tank cleaning process, while the sample was determined purposively, namely officers and crew directly involved in these activities. The research instrument was the researcher with data analysis through data reduction, data presentation, and drawing conclusions. The results showed that efforts to prevent damage were carried out through checking the condition of the equipment, checking the nozzle and connections, proper installation, and routine maintenance after use. Obstacles found included unstable water pressure, nozzle wear, suboptimal Butterworth rotation, and imprecise installation. This study concluded that consistent inspection, regular maintenance, precise installation, and water pressure control are the main factors in minimizing Butterworth damage and optimizing the tank cleaning process.